Types of organizational management structures and their positive and negative aspects - Khanenko, A. (Економічний вісник Донбасу, 2025)
The article reveals the meaning of the concept of organizational structure; approaches to the formation of the management structure were studied, a typology of organizational structures was formed, their advantages and disadvantages, and the possibilities of application for building a competent organization were determined. The role of the organizational management structure in the effective functioning of the enterprise, in the maximum combination of various types of activities and divisions of the organization is defined. A variety of types of organizational structures are presented. The main types of organizational structures are distinguished: mechanistic structures (or bureaucratic, hierarchical) and organic structures (or adaptive, flexible). The traditional types of organizational structures existing today are described: linear, functional, linear-functional, linear-headquarters, divisional, which are characterized by a rigid hierarchy of power in the company, formalization of rules and procedures, centralized decision-making. The peculiarities of adaptive organizational structures of entrepreneurial-type organizations are revealed, which are characterized by the blurring of the management hierarchy, a small number of management levels, flexibility of the power structure, decentralization of decision-making, and widely determined responsibility in activities. The characteristics of the types of organizational structures of the adaptive type are given: cross-functional structure of organizational management; project organizational management structure; matrix organizational structures; conglomerate organizational forms of management; network organizational structure; virtual organization. У статті розкрито значення поняття організаційної структури; досліджено підходи до формування структури управління, сформовано типологію організаційних структур, визначено їх переваги та недоліки, а також можливості застосування для побудови компетентної організації. Визначено роль організаційної структури управління в ефективному функціонуванні підприємства, у максимальному поєднанні різних видів діяльності та підрозділів організації. Представлено різноманітні типи організаційних структур. Виділено основні типи організаційних структур: механістичні структури (або бюрократичні, ієрархічні) та органічні структури (або адаптивні, гнучкі). Описано традиційні типи організаційних структур, що існують сьогодні: лінійні, функціональні, лінійно-функціональні, лінійно-штабні, дивізіональні, які характеризуються жорсткою ієрархією влади в компанії, формалізацією правил і процедур, централізованим прийняттям рішень. Розкрито особливості адаптивних організаційних структур організацій підприємницького типу, які характеризуються розмиттям ієрархії управління, невеликою кількістю рівнів управління, гнучкістю структури влади, децентралізацією прийняття рішень, широко визначеною відповідальністю в діяльності. Наведено характеристики типів організаційних структур адаптивного типу: міжфункціональна структура управління організацією; проектна структура управління організацією; матричні організаційні структури; конгломератні організаційні форми управління; мережева організаційна структура; віртуальна організація.